C-Reactive Protein (CRP) and Autoimmune Disease: Facts and Conjectures - Alexander J. Szalai (Clinical and Developmental Immunology)
C-reactive protein (CRP) is a blood component comprised of five identical subunits with a combined molecular mass of 110 kDa; in the presence of Ca++ it binds phosphocholine (PC) with high affinity. Ligand-bound CRP activates complement and the protein reportedly binds various Fc receptors. Coincident with a now decade-long resurgence in clinical interest in associations of CRP with disease, our laboratory has been investigating the biology of CRP in vivo using human CRP transgenic mice (CRPtg). At that time we confirmed that CRP affects a host defense function mediated at least in part through the elimination of pathogens. Less appreciated and not as well understood as CRP's ability to bind antigen and aid in the elimination of microbes, is its known ability to bind autoantigens and presumed capacity to promote clearance of apoptotic cells. These latter properties of CRP have long been suspected to contribute to homeostasis and to autoimmune disease. In this article we review and update the evidence generated in CRPtg by our group and in vitro by others' that indicates CRP is more than just an antimicrobial molecule and convenient marker of inflammation - rather, it protects against autoimmunity. A mechanistic hypothesis is presented to account for this cause-and-effect relationship.